Why Is It Okay to Deceive the Public: Should Public Relations Firms and Ad Agencies Be Required to Disclose the Sponsors of Astroturfing and Other Masked Persuasion Practices? - Henke, Lucy L. (Journal of Marketing Development and Competitiveness, 2018)
Astroturfing and other masked persuasion practices beg the question of whether public relations firms and ad agencies that hire crisis actors, arrange false flag events, or otherwise engage in attempts to deceive should be held to the same disclosure standard imposed by the FTC on other forms of commercial communication. To the extent that sponsors of these deceptive practices benefit in material ways at the expense of “reasonable” and unsuspecting consumers, should the actors and their sponsors be required to disclose the sponsorship? Alternatively, would attempts to increase consumer awareness of the practices, to eliminate the deception, obviate the need for regulation?